ANALISIS PERAN KOMPETENSI, PELATIHAN DAN BUDAYA ORGANISASI TERHADAP KINERJA PEGAWAI MELALUI KEPUASAN KERJA PADA KEMENTERIAN LINGKUNGAN HIDUP - Evitasari Evitasari; Hamsinah Hamsinah; Umi Rusilowati (CV. KAMPUS AKADEMIK PUBLISHING, 2026)
Abstract. This study aims to analyze the role of training competencies and organizational culture on employee performance through job satisfaction at the Ministry of Environment. The high demands for precision and workload in the public sector serve as the primary background for examining the factors that drive civil servant productivity. The research method used was quantitative with a descriptive and causal approach. Data were collected through questionnaires distributed to 328 respondents, employees of the Ministry of Environment. The data analysis technique used Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) to test direct and indirect relationships between variables. The results showed that of the seven proposed hypotheses, five were accepted and two were rejected. Partially, Organizational Culture had a positive and significant effect on Job Satisfaction and Employee Performance. Competence and Training were shown to have a significant positive effect on Employee Performance, but not on Job Satisfaction. Furthermore, Job Satisfaction has been shown to have a significant positive influence on Employee Performance and acts as a mediating variable, particularly in the relationship between Organizational Culture and Performance. Interesting findings in this study indicate inequalities in compensation (Tukin) and workload, although overall employee performance remains in the very good category. It is recommended that agencies conduct an evaluation of their environmental information systems to close technical gaps and improve training methods to be more practical/simulation-based to optimize employees' growth mindset potential. Keywords: Competence, Training, Organizational Culture, Job Satisfaction, Employee Performance, SEM-PLS